Analysis of the Negative Impacts of Gadget Use on Early Adolescents - Siti Maisaroh; Muhammad Takwin Machmud (International Journal of Educational Practice and Policy, 2025)
The purpose of this study is to analyze the negative impacts of gadget use on early adolescents. The presence of gadgets, particularly in the form of smartphones, has significantly contributed to daily life as a medium for information retrieval, interaction, entertainment, and even online business activities. The advancement of information and communication technology is increasingly benefiting society. Gadgets, as one of the products of this technology, have transformed human communication behavior by transcending space and time. A gadget is a small electronic device with specific functions, such as a smartphone. Essentially, this technology was created to make human life easier and more comfortable. However, the rapid technological advancements today have made it nearly impossible to find any area of human life untouched by their use, whether directly or indirectly. Along with globalization and the demand for rapid information exchange, negative impacts on early adolescents have emerged. These impacts include health issues, educational challenges, disruptions in social interaction, and even effects on family economics. Excessive gadget use among early adolescents can trigger harmful side effects such as an increased risk of depression, health problems, anxiety disorders, difficulty focusing, and other problematic behaviors. Gadget addiction can also hinder adolescents from socializing with their surroundings and increase the risk of loneliness. The role of parents is crucial in setting boundaries to prevent gadget addiction among children and mitigate these risks.